Beefalin: meat tenderizer from non-edible parts of pineapple - Aizi Nor Mazila, Ramli; Normaiza, Z.; Farah Hanani, Zulkifli; Hazrulrizawati, Hamid; Rohaida, Che Man (2018)
Several strategies have been implemented to improve tenderness quality of meat. Meat tenderization using plant proteolytic enzymes are preferable. Pineappleby-products(nonedibleparts)–sourceofproteolytic enzyme(bromelain). Higher demand in pineapple processed items-huge pineapple by-products generations. Pineappleby-products are typically easily exposed to microbial spoilage OBJECTIVE: to find out the added value of the pineapple by products, stem, from the Malaysian variant of A.comosus to be used a same attenderizer.